Waldorf early childhood care and education in the 21st century - Taplin, Jill Tina (Frontiers in Education, 2024)
Many of the elements of the Waldorf approach featured 100 years ago, with the opening of the first Waldorf early childhood groups, are now supported by current evidence and research into child development. Waldorf practitioners are developing stronger and better-informed practice based on the founding principles, contemporary resources and an ever-deepening understanding of young children today. In this paper I intend to explore five of the significant themes which have received additional impetus in recent years. 1. In the Waldorf approach a foundation of social and emotional development is prioritised as a support for later cognitive development. 2. A key features of the Waldorf early childhood environment is that it is a sensorily-friendly and unhurried microcosm of everyday life. 3. Waldorf practitioners and teachers have been actively promoting for the past century the importance of building up children’s connections with nature. 4. As a result of increased academicization and the pressures of 21st century life, child-initiated, free, creative play is under threat and needs protection and support. 5. One aspect of the Waldorf approach viewed as key is that the inner development of the practitioner or teacher is just, if not more, important than their outer work. Following this review of some essential aspects of the Waldorf approach in the light of recent development, the paper concludes by looking into the future and pinpointing three aspects at the forefront of developments and research among Waldorf early childhood practitioners today.